Barriers to Application of Communicative Skills by Nurses in Nurse-Patient Interaction: Nurses and Patients’ Perspective - Aghabarary; Varvani-Farahani; Mohammadi (نشریه پرستاری ایران, 2009)
Background and Aim: The main role of a nurse is caring. To take care of patients is achievable only through communicating them, but, the results of previous studies have revealed that due to lack of communicative skills, nurses are unable to communicate properly, a problem about which patients keep complaining very often. The present study is an attempt to determine the barriers to application of communicative skills by nurses from the perspectives of nurses and patients.   Material and Method: This study is descriptive analytical study and adopts a problem– solving perspective. The research samples (90 nurses and 45 patients) were selected through simple sampling method from two academic hospitals affiliated to Tehran University of Medical Sciences and Health services (Imam Khomeini and Valiy-e ASR). Two survey instruments within Lickert scale format were designed separately for two groups of nurses and patients. The instruments contained the barriers to application of communicative skills by nurses. These barriers were classified into four categories: barriers related to nurses, patients, nurses and patients and environment. Data were analyzed using descriptive and analytical statistics.   Results: The results showed that from the nurses’ perspective the most and the least important barriers were patient– related communication barriers, and nurse– patient-related communication barriers, respectively Whereas from the patients’ perspective, the most and the least important barriers were nurse– related communication barriers, and nurse- patient related communication barriers, respectively.   Conclusion: Nurses consider factors specific to patient as the most important barriers for nurses to use their communicative skills yet for patients those specific to nurses were selected as the most important barriers. A strategy entitled “Establishing a Committee for Ensuring Quality of Nursing Services with an Emphasis on Nurses’ Communicative Skills" was proposed to increase use of communicative skills by nurses when interacting with patients.